2023
DOI: 10.3390/cryst13050830
|View full text |Cite
|
Sign up to set email alerts
|

Towards Closed-Loop Recycling of Ceramic Particle-Reinforced Aluminium Alloys: Comparative Study of Resistance-Heating Sintered Primary and Solid-State Recycled Secondary SiCp/AlSi7Mg Composites

Abstract: Particle-reinforced aluminium matrix composites (AMC) with a high-volume fraction of ceramic reinforcement (>30 vol.%) combine high specific strength and stiffness with good wear resistance and thermal stability, resulting in their increasing popularity in high-load applications, such as brake discs and bearings. It is hence assumed that AMC will accumulate as scrap in the near future. Appropriate recycling strategies must therefore be developed to maintain AMC’s inherent properties. Melt-metallurgical recy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…During this sintering process, the powder was heated by its own electrical resistance or indirectly by the used graphite tool. Due to the high heating and cooling rates, sintering temperatures close to the solidification temperature as well as the high sintering pressures, the used powder can be consolidated within a very short time in the range of few minutes [36]. Based on expertise from previous investigations [2,37], the sintering process was carried out in a vacuum for 5 min (holding time) at 520 • C and at a sintering pressure of 50 MPa to achieve nearly fully dense bodies (porosity < 1%) within a very short time to avoid microstructural coarsening effects.…”
Section: Materials and Processingmentioning
confidence: 99%
“…During this sintering process, the powder was heated by its own electrical resistance or indirectly by the used graphite tool. Due to the high heating and cooling rates, sintering temperatures close to the solidification temperature as well as the high sintering pressures, the used powder can be consolidated within a very short time in the range of few minutes [36]. Based on expertise from previous investigations [2,37], the sintering process was carried out in a vacuum for 5 min (holding time) at 520 • C and at a sintering pressure of 50 MPa to achieve nearly fully dense bodies (porosity < 1%) within a very short time to avoid microstructural coarsening effects.…”
Section: Materials and Processingmentioning
confidence: 99%
“…Among several process conditions, the authors found an optimum set of parameters to achieve recovery rates of 84% for the matrix alloy and 98% for SiC particles. Hirsch et al [21] recently investigated a solid-state recycling route for aluminum matrix composites with a high-volume fraction of ceramic reinforcement. They concluded that the contamination level of the milled composite and consolidation method significantly influenced the properties of the recycled MMC.…”
Section: Introductionmentioning
confidence: 99%